Inhibition of Inflammation and Bone Erosion by RNA Interference–Mediated Silencing of Heterogeneous Nuclear RNP A2/B1 in Two Experimental Models of Rheumatoid Arthritis. Issue 9 (September 2015) - Herman, Sonja; Fischer, Anita; Presumey, Jessy; Hoffmann, Markus; Koenders, Marije I.; Escriou, Virginie; Apparailly, Florence; Steiner, Guenter
<x xml:space="preserve">Abstract</x> Objective The nuclear protein heterogeneous nuclear RNP A2/B1 (hnRNP A2/B1) is involved in posttranscriptional regulation of gene expression. It is constitutively expressed in lymphoid organs and highly up‐regulated in the synovial tissue of patients with rheumatoid arthritis (RA), who may also generate autoantibodies to this protein. This study was undertaken to investigate the potential involvement of hnRNP A2/B1 in the pathogenesis of autoimmune arthritis, by silencing hnRNP A2/B1 expression in 2 animal models of RA. Methods Collagen‐induced arthritis (CIA) and the K/BxN serum–transfer model were used as animal models of RA. Efficient silencing of hnRNP A2/B1 was achieved using a liposome‐based carrier system for delivery of small interfering RNAs. Expression of hnRNP A2/B1 was analyzed by flow cytometry, reverse transcription–quantitative polymerase chain reaction, Western blotting, and immunohistochemistry. The number of osteoclasts was determined by tartrate‐resistant acid phosphatase staining. Cytokine levels and anticollagen antibody levels were measured by enzyme‐linked immunosorbent assay. Results Efficient silencing of hnRNP A2/B1 was achieved in all lymphoid organs. In both experimental models, the incidence and severity of arthritis were largely reduced and bone erosion was not detectable as compared to the control groups. Down‐modulation of hnRNP A2/B1 significantly interfered with the production of proinflammatory cytokines from monocyte/macrophages, but not from T cells. Consistent with these findings, production of T cell cytokines was not impaired when cells were restimulated in vitro with type II collagen. Furthermore, levels of anticollagen antibodies were not affected by hnRNP A2/B1 silencing. Conclusion Our findings suggest that hnRNP A2/B1 has an important role in regulation of the innate immune system, especially at the level of monocyte/macrophage activation. Therefore, down‐modulation of hnRNP A2/B1 seems to affect primarily the effector phase of autoimmune arthritis.